Energy Independence Risk and Energy Policy Risk: Theory and Empirical Testing - Pardaev, Jamshid; Matyokubova, Dilfuza; Isaev, Fakhriddin; Ibadullaev, Ergash; Merza, Ebrahim; Sabirov, Khamid; Rajabov, Nazirjon (International Journal of Energy Economics and Policy, 2025)
The study investigates the unique relation in the middle of regulatory risk in the energy sector and energy independence risk across 135 countries from 2000 to 2023. The method of moments quantile regression (MMQR) is conducted for the empirical estimations along with the second generation methods such as CIPS unit root and Westerlund cointegration tests. The outcomes illustrate a vital positive effect of power policy risk on energy independence risk across all the (10%-90%) quantiles of the regression. The policy implications are provided to consider the function of energy policy in achieving fuel independence.